PERSEPSI PEMILIH TENTANG KAMPANYE KOTAK KOSONG : KASUS BERITA TIRTO.ID PADA PEMILU 2024 - Nazwa Putri Septiani; Chika Rahma Aulia; Rakha Ahmad Ramadhan; Muhammad Haikal; Pia Khoirotun Nisa (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2025)
shows that there are segments of society who feel they are not represented by the existing candidates. The high number of blank ballots indicates that many voters are dissatisfied with the choices available, so they choose not to vote for a candidate at all. This is a clear signal for political parties and candidates to listen more to the voice of the people. The implementation of campaigns is regulated in National Security Council Decree Number 11640 dated 2 May 1955. This decision does not determine the period for the campaign, but only states that the campaign ends the day before the voting. In Indonesia, the "empty box" phenomenon in general elections is an important issue that reflects the political dynamics and challenges faced by the democratic system. The empty box is one of the choices that voters can make in general elections when they feel there is no worthy candidate to nominate. In the context of the Pilkada, an empty box is not just an option not to vote, but a symbol that represents deep dissatisfaction with the existing candidates and the prevailing political system. With an empty box, people can express their dissatisfaction directly and signal to the political system that they want change, including a symbol of protest against candidates and a boost to political awareness. In this case, the mass media plays an active role in distributing information as an intermediary for the community using communication tools.